What Are The Factors That Affecting The Usage Of Bank Jago Application? - Yudha Mahardika; Viany Utami Tjhin (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to identify the causes that affecting Bank Jago Usage. Starting from a Conventional Bank (Head Quarter) in Bandung in 2019 and now in 2023, Bank Jago already has moved to Jakarta as a Digital Bank, with more than 5 million users. Yet the users still found some weaknesses while using the Bank Jago Application on transferring money, using the features, and making an account. Spreading questionnaires was conducted to Bank Jago Application users, who live in Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi). 136 People was filled the questionnaire as voluntary. Technology Acceptance Model (TAM) and Self-Service Technology (SST) research model was used in this study. The result has been proven that there are two factors, which is Convenience and Perceived Ease of Use. Thus, for future development, from this study, the developer can add some more futures. Such as using the digital wallet by Face Recognition and Fingerprint as Authentication code. The Data processing was using Smart PLS (Structural Equational Modelling) V.3.2.9.